Belize : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This paper provides background information and analysis of recent economic developments and relevant issues in Belize. The main differences between the high growth experiences in the late 1980s and during 1999-2000 are also discussed. The following statistical data are presented in detail: savings and accounts, main agricultural crops, acreage, and production; industrial production, operations of the central government, interest rates, treasury securities, consumer price index, principal domestic exports, sugar exports by destination, direction of trade, terms of trade, summary of tax system, and so on.